2021
DOI: 10.1016/j.dcn.2021.101000
|View full text |Cite
|
Sign up to set email alerts
|

Miswiring the brain: Human prenatal Δ9-tetrahydrocannabinol use associated with altered fetal hippocampal brain network connectivity

Abstract: Increasing evidence supports a link between maternal prenatal cannabis use and altered neural and physiological development of the child. However, whether cannabis use relates to altered human brain development prior to birth, and specifically, whether maternal prenatal cannabis use relates to connectivity of fetal functional brain systems, remains an open question. The major objective of this study was to identify whether maternal prenatal cannabis exposure (PCE) is associated with variation in human brain hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…In addition to shedding light on the origins of typical neural development, fetal RSFC studies also inform our understanding of health risk. For instance, exposures like prenatal stress ( Thomason et al, 2021a ), cannabis ( Thomason et al, 2021b ), and lead ( Thomason et al, 2019 ) have been linked to altered fetal neurodevelopment, which has important implications for policy and intervention. Taken together, this work highlights that fetal MRI is a crucial tool for understanding typical and atypical human neurodevelopment and for uncovering the earliest origins of disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to shedding light on the origins of typical neural development, fetal RSFC studies also inform our understanding of health risk. For instance, exposures like prenatal stress ( Thomason et al, 2021a ), cannabis ( Thomason et al, 2021b ), and lead ( Thomason et al, 2019 ) have been linked to altered fetal neurodevelopment, which has important implications for policy and intervention. Taken together, this work highlights that fetal MRI is a crucial tool for understanding typical and atypical human neurodevelopment and for uncovering the earliest origins of disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…This is also the first study to longitudinally examine the impacts of THC on fetal brain development across gestation using in utero MRI techniques. A prior human study examined the impact of prenatal cannabis exposure on human fetal brain hippocampal functional connectivity using functional MRI at a single time point in the mid-third trimester 30 . Thomason et al 30 , found that maternal cannabis use was associated with changes in the fetal neural connectome, specifically fetal dorsolateral, medial and superior frontal, insula, anterior temporal, and posterior cingulate connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Without additional information about the relevance of this hippocampal difference to future development, it is difficult to interpret this elevated connectivity as a risk or protective response in the brain, or to determine whether it is a transient association without long-term ramifications for child development. Although stress-related neural differences are often conceptualized as harmful in nature, one study found that relatively stronger functional coupling between the hippocampus and posterior parietal cortex in fetuses was prospectively correlated with fewer behavioral and executive functioning problems and greater school readiness at age five [ 60 ]. It is therefore possible that our finding of stronger fetal hippocampus–parietal connectivity in the context of acute stress may be an adaptive neural response that prepares offspring to navigate changing environments.…”
Section: Discussionmentioning
confidence: 99%